Respuesta :

9514 1404 393

Answer:

  D.  h(x) = 5x² +12x +9

Step-by-step explanation:

The final constants are mostly different, so you can simplify your work by just figuring that one.

  h(x) = g(x) -f(x)

  h(0) = g(0) -f(0) = -7 -(-16) = +9 . . . . . matches choice D

__

If you want to figure the whole expression ...

  h(x) = g(x) -f(x)

  h(x) = 12x² +7x -7 -(7x² -5x -16)

  h(x) = 12x² +7x -7 -7x² +5x +16

  h(x) = (12 -7)x² +(7 +5)x +(-7 +16)

  h(x) = 5x² +12x +9 . . . . . matches choice D

ACCESS MORE